Watch winder based on the internet of things - Leonardo Kamajaya; Fitri Fitri; Mocharief Azzmi Santoso (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Watches are wearable devices that support human activities as timepieces. There are two types of watches based on their source driving energy: the quartz type, which uses a battery, and the automatic mechanical type, which uses a mechanical mechanism to convert the kinetic energy obtained when the clock is used as the energy to drive the hands. Automatic mechanical type watches have a time limit of 48 hours or two days until the energy turns off and the time stop. Therefore, a watch winder is needed to make movements to keep the automatic watch running while not in use. So, users can use their watch again without the need to adjust the time, date and other functions. The watch winder produced in this study employs a stepper motor that is controlled by an ESP32 microcontroller via a ULN2003 motor driver integrated circuit (IC). This type of stepper motor is used because it has a high rotor rotation precision to prevent the clock from over-winding problems. This watch winder device also has a watch condition monitoring feature through application-based temperature and humidity parameters. Users can monitor the condition of their watch and control the dial of the watch winder’s modules through the integrated application.